Activation of HIV-Specific CD8+ T-cells from HIV+ Donors by Vesatolimod. Issue 3 (April 2020) - Ram, Renee R; Duatschek, Paul; Margot, Nicolas; Abram, Michael; Geleziunas, Romas; Hesselgesser, Joseph; Callebaut, Christian
Background: Vesatolimod (VES; GS-9620) is a Toll-like receptor 7 (TLR7) agonist that directly activates human plasmacytoid dendritic cells (pDCs) and B lymphocytes resulting in direct and indirect production of cytokines and immune activation. VES is being evaluated in HIV-1-infected people as part of an HIV remission strategy. Here we investigated the potential of VES to trigger indirect activation of HIV-specific CD8 + T-cells using immune cell cultures derived from HIV+ donors. Methods: Peripheral blood mononuclear cell (PBMC) cultures derived from HIV+ donors virologically suppressed on stable antiretroviral therapy ( n =31) were isolated and treated with VES or vehicle for 24 h. Cells were stained with surface and intracellular fluorescent conjugated antibodies and HIV-specific pentamers, and analysed by flow cytometry. Results: Treatment of PBMCs with VES resulted in all 31 donors demonstrating a concentration dependent increase in CD8 + T-cell activation (CD69 + ) of up to 88%. Of these donors, 20 of 31 donors displayed a concentration-dependent increase in HIV-specific CD8 + T-cell activation due to VES with a maximum of 20.8%. Intracellular staining was performed in a subset of donors ( n =14), 5 of which displayed VES-induced activation of functional HIV-specific CD8 + T-cells as assessed by CD107a and/or tumour necrosis factor (TNF)-α upregulation. Conclusions: This study demonstrates that VES treatment can induce the activation of functional HIV-specific CD8 + T-cells in donor derived PBMCs. These data support the potential use of VES to activate functional HIV-specific CD8 + T-cells as part of an HIV remission strategy.